'I miss my family, it's been a while…' A qualitative study of clinicians who live and work in rural/remote Australian Aboriginal communities. (23rd December 2016) - Irving, Michelle; Short, Stephanie; Gwynne, Kylie; Tennant, Marc; Blinkhorn, Anthony
Abstract: Objectives: Dental issues are more prevalent for Aboriginal Australians, especially those living in rural/remote locations, but distribution of clinicians is favoured towards metropolitan areas and are not always culturally competent. This study aimed to document the experiences of dental clinicians who relocated to rural/remote communities to provide dental services to Aboriginal communities in an effort to redress these gaps. Setting: Clinicians working in a new rural/remote dental service strategy to Aboriginal communities in Northern NSW. Design: Qualitative semi‐structured face‐to‐face interviews and reflective diaries were analysed qualitatively. Participants: Relocating dental clinicians and their support team. Results: Three major themes emerged: Theme one: Mastering the clinical environment through professional experiences: Increasing professional capabilities, clinical environment, valuing team work and gaining community respect. Theme two: Development and growth of the individual through personal and social experiences: culture shock, developing cultural competence, social impact, economic cost and personal adjustments and growth. Theme three: An overarching sense of achievement and advice to new clinicians. Conclusion: Relocation to rural and remote communities to provide health services is a complex but rewarding process. Providing personal and professional support, to relocating clinicians resulted in an overall positive experience for the participants, where they increased their professional skills and developed personally. Living and working in the community increased their cultural competence. Barriers were overcome through effective communication, flexibility and teamwork. Funding for rural placements, such as these, is critical for rural and remote health services and should include long‐term appropriate funding for mentoring and support.